Why do we have to move fluid to be able to breathe? - Fronius, Martin; Clauss, Wolfgang G.; Althaus, Mike; Justus Liebig University Giessen (My University, 2012)
The ability to breathe air represents a fundamental step in vertebrate evolution that was accompanied by several anatomical and physiological adaptations. The morphology of the air-blood barrier is highly conserved within air-breathing vertebrates. It is formed by three different plies, which are represented by the alveolar epithelium, the basal lamina and the endothelial layer. Besides these conserved morphological elements, another common feature of vertebrate lungs is that they contain a certain amount of fluid that covers the alveolar epithelium. The volume and composition of the alveolar fluid is regulated by transepithelial ion transport mechanisms expressed in alveolar epithelial cells. These transport mechanisms have been reviewed extensively. Therefore, the present review focuses on the properties and functional significance of the alveolar fluid. How does the fluid enter the alveoli? What is the fate of the fluid in the alveoli? What is the function of the alveolar fluid in the lungs? The review highlights the importance of the alveolar fluid, its volume and its composition. Maintenance of the fluid volume and composition within certain limits is critical to facilitate gas exchange. We propose that the alveolar fluid is an essential element of the air-blood barrier. Therefore, it is appropriate to refer to this barrier as being formed by four plies, namely (1) the thin fluid layer covering the apical membrame of the epithelial cells, (2) the epithelial cell layer, (3) the basal membrane, and (4) the endothelial cells.
Keywords: air-breathing; vertebrates; alveolar fluid; functional significance; review; ddc:570